Association of genetic variants in MIR17HG and in the promoter of MIR17HG with susceptibility to cancer in Chinese Han population: a systematic review and meta-analysis - Binghua Tong; Zhaonan Zhang; Zhaowei Xu; Yangyang Yang (BMC Cancer)
Abstract Background The association between microRNA 17–92 cluster host gene (MIR17HG) polymorphisms and the risk of cancer has been evaluated in studies, here, we attempted to elucidate the relationship between 6 single nucleotide polymorphisms (SNPs) of MIR17HG (rs17735387 G > A, rs7336610 C > T, rs1428 C > A, rs7318578 A > C, rs72640334 C > A, and rs75267932 A > G), 3 SNPs in the promoter of MIR17HG (rs9588884 C > G, rs982873 T > C, and rs1813389 A > G) and susceptibility to cancer in Chinese Han population. Methods Systematic literature research from databases were performed with strict eligibility criteria to include the relevant studies for this meta-analysis. Association between the SNPs of MIR17HG and cancer risk was estimated by pooling the odds ratios (ORs) with 95% confidence interval (95% CI) in five genetic models (allelic model, dominant model, recessive model, homozygous model, and heterozygous model). Results The pooled meta-analysis showed that there was no significant association between rs17735387 G > A, rs7336610 C > T, rs1428 C > A, rs7318578 A > C, rs72640334 C > A, and rs75267932 A > G and cancer risk in Chinese Han population. However, for the SNPs in the promoter of MIR17HG, rs9588884 C > G and rs982873 T > C could decrease cancer risk in most genetic models, but not rs1813389 A > G. Conclusion This present meta-analysis identified 2 SNPs in the promoter of MIR17HG (rs9588884 C > G and rs982873 T > C) may be protective factors against cancer in Chinese Han population.